Densification behaviour and sintering mechanisms of Cu- or Co-doped SnO2 : a comparative study - Zhang, T. S. (2014)
Compared with the CuO–SnO2 system, there is a lack of experimental evidence of a eutectic liquid phase in the CoO–SnO2 system. It is therefore believed that the densification behaviour and sintering mechanisms of the two systems are completely different. However, our present study clearly demonstrated that the Co- and Cu-doped SnO2 ceramics exhibited a similar densification behaviour. The 1 wt.% Cu- or Co-doped SnO2 ceramics could reach over 95% relative density when sintered to 1250 °C with a heating rate of 5 °C min−1. It was found that both CoO4/3- and CuO-doped SnO2 follow the same mass transport mechanism – viscous flow sintering during early-stage sintering. This was verified with the classic isothermal and constant-heating-rate models, as well as Frenkel’s viscous flow theory. The viscous flow mechanism dominated densification up to ∼73 and ∼78% relative density with the apparent activation energies of 362 and 440 kJ mol−1 for Co and Cu doping cases, respectively.